Riskante digitale Transformation Fortsetzung der Literaturumschau innerhalb wie außerhalb von Theologie und Kirche - Thiede, Werner (Theologische Rundschau, 2022)
In recent years there have been many books euphoric about as well as critical of digitization: This report continues the collective review in ThR 84/3 (2019). It is here divided into two halves: The first main part informs about literature outside of theology and church, namely about 1) problem perceptions from an economic perspective, 2) legal aspects of artificial intelligence, 3) human and natural science criticism of digitization, 4) philosophical and 5) anthroposophical new research on the topic. The second part is devoted to theological and religious studies books that deal with the digital transformation, including those that deal more or less uncritically with the topic, which is so highly relevant in terms of individual, social and church policy.
CRIS-Team Scopus Importer:2022-07-15